2021
DOI: 10.1111/sms.13963
|View full text |Cite
|
Sign up to set email alerts
|

One year of Football Fitness improves L1–L4 BMD, postural balance, and muscle strength in women treated for breast cancer

Abstract: Purpose To examine efficacy of 12 months Football Fitness offered twice per week on bone mineral density (BMD), bone turnover markers (BTM), postural balance, muscle strength, and body composition in women treated for early‐stage breast cancer (BC). Methods Women treated for early‐stage BC were randomized to Football Fitness (FFG, n = 46) or control (CON, n = 22) in a 2:1 ratio for 12 months, with assessments performed at baseline, 6 months and 12 months. Outcomes were total body‐, lumbar spine‐ and proximal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Our findings emphasise the potential of football as a versatile and effective type of training that can be used to provide broad-spectrum fitness, well-being, and health effects for a variety of population groups. The data support other observations in children [28], sedentary adults [1][2][3], elderly [29,30], and various patient groups with hypertension, type 2 diabetes, and cancer [31][32][33]. In most regions, the COVID-19 pandemic has reduced physical activity among the general public [16] and simultaneously increased sedentary and screen time in children and adults [17,34].…”
Section: Discussionsupporting
confidence: 84%
“…Our findings emphasise the potential of football as a versatile and effective type of training that can be used to provide broad-spectrum fitness, well-being, and health effects for a variety of population groups. The data support other observations in children [28], sedentary adults [1][2][3], elderly [29,30], and various patient groups with hypertension, type 2 diabetes, and cancer [31][32][33]. In most regions, the COVID-19 pandemic has reduced physical activity among the general public [16] and simultaneously increased sedentary and screen time in children and adults [17,34].…”
Section: Discussionsupporting
confidence: 84%
“…As a result, seven reports were included in the review: five RCTs [ 18 , 26 , 27 , 28 , 29 ] and two pilot CTs [ 30 , 31 ]. The process of searching and selecting trials is outlined in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The methodological quality of the five RCTs was assessed on the PEDro scale using the following score ranges: low quality: 1–4 pts (two trials [ 18 , 28 ]); medium quality: 5–7 pts (three trials [ 26 , 27 , 29 ]), and high quality: 8–9 pts (zero trials) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although most investigations have not assessed the presence or absence of AEs [ 54 , 55 , 57 , 58 , 59 , 62 , 63 , 66 , 68 , 70 , 72 ], the reported findings support the safety profile of exercise [ 56 , 61 , 62 , 64 , 65 , 67 , 69 , 71 , 73 , 74 , 75 ]. In trials including patients with cancer at high risk of accelerated bone loss, e.g., those undergoing chemotherapy, endocrine therapy, or in postmenopausal status, the majority did not find any serious AEs [ 56 , 62 , 64 , 65 , 69 , 71 , 74 ], while three registered mild side effects [ 61 , 74 , 75 ]. For instance, Nikander and colleagues, in their randomized controlled trial, which consisted of a 12-month exercise intervention involving patients with breast cancer undergoing endocrine therapy, recorded 4 moderate AEs [ 61 ].…”
Section: Exercise and Bone Lossmentioning
confidence: 96%
“…Analyzing the trials, which included patients at high risk of losing bone, some reported the inability of exercise to preserve bone in patients with cancer [ 56 , 65 , 66 , 68 , 70 , 71 ]. On the other hand, different investigations found improvements in bone mineral density among patients at high risk of losing bone tissue, even if considerable heterogeneity regarding the skeletal sites has been observed [ 59 , 60 , 62 , 64 , 69 , 74 , 75 ]. For instance, a 12-month randomized controlled trial, including 498 patients with breast cancer treated with chemotherapy and/or radiotherapy and/or undergoing endocrine treatments, has explored the impact of a supervised weekly aerobic or circuit training plus home-based, vigorous-intensity aerobic activity 2–3 times per week on bone tissue.…”
Section: Exercise and Bone Lossmentioning
confidence: 99%